Respuesta :

Answer:

Proved

Step-by-step explanation:

Given

[tex](2 * 10^2) * (3 * 10^5) = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Required

Prove

On the right hand side, we have:

[tex]2 * 10^2 * 3 * 10^5 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Rewrite:

[tex]2 * 3* 10^2 * 10^5 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

[tex]6* 10^2 * 10^5 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Apply law of indices

[tex]6* 10^{2+5} = 3.5 * 10^7 + 2.5 * 10^7[/tex]

[tex]6* 10^7 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Express 6 as 3.5 + 2.5

[tex](3.5 + 2.5)* 10^7 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Open bracket

[tex]3.5 *10^7+ 2.5*10^7 = 3.5 * 10^7 + 2.5 * 10^7[/tex]

Proved

ACCESS MORE